Penerapan aplikasi game wordwall tipe gameshow quiz untuk meningkatkan minat belajar siswa pada materi Dinasti Umayyah di Andalusia - Sahro, Khoirus (Maliki Interdisciplinary Journal, 2024)
This research aims to examine the effectiveness of implementing the Gameshow Quiz type Wordwall game application in increasing students' interest in learning about the Umayyad Dynasty material in Andalusia. Interest in learning is an important factor that influences student learning outcomes. However, learning history is often considered boring and less interesting for students. Therefore, innovation is needed in learning methods to attract student interest. The Gameshow Quiz type Wordwall application was chosen because it offers an interactive and fun approach to the teaching and learning process. This method is expected to increase students' active participation and make history learning more interesting and enjoyable. This research uses a quasi-experimental method with a pretest-posttest control group design. The research subjects were class X students at MA Maarif Sukorejo who were divided into two groups: an experimental group that used the Wordwall application and a control group that used conventional methods. Data was collected through learning interest questionnaires given before and after the intervention, as well as observations during the learning process. The results showed that there was a significant increase in students' interest in learning in the experimental group compared to the control group. Students who learn using the Wordwall application show higher enthusiasm and involvement in learning. They are also more active in discussing and answering questions compared to students who study using conventional methods. The conclusion of this research is that the application of the Gameshow Quiz type Wordwall game application is effective in increasing students' interest in learning about the Umayyad Dynasty material in Andalusia. The application of technology and interactive methods in history learning can be a solution to overcome boredom and increase student engagement. This research recommends using the Wordwall game application in history learning to increase student interest and learning outcomes.